2012
DOI: 10.1503/cmaj.120256
|View full text |Cite
|
Sign up to set email alerts
|

Postobstructive pulmonary edema associated with a substernal goitre

Abstract: A 50-year-old woman had experienced 6 months of mild shortness of breath and noise while breathing. She was obese with a body mass index of 32. Her primary care physician found a neck mass; results of a serum thyroid function test were normal. Her symptoms remitted spontaneously, and she ignored advice to seek further evaluation. Six months later, she had her first episode of dyspnea with cyanosis, followed by decreased consciousness. When the ambulance arrived, her Glasgow Coma Scale score was 7 and her perip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Although diuretics are often used, their role is uncertain in NPPE [8]. Diuretics may also worsen hypoperfusion and exacerbate a pre-existing hypovolemia [9].…”
Section: Discussionmentioning
confidence: 99%
“…Although diuretics are often used, their role is uncertain in NPPE [8]. Diuretics may also worsen hypoperfusion and exacerbate a pre-existing hypovolemia [9].…”
Section: Discussionmentioning
confidence: 99%
“…There have been cases reported in the literature describing postobstructive pulmonary edema after total thyroidectomy due to rapid relief of significant tracheal compression. 30,31 In addition, many studies have documented an increased risk of recurrent laryngeal nerve palsy following thyroidectomy for large retrosternal goiter. 3,4,32 Prolonged intubation may predispose these patients to developing DVT/PE, with increased rates being seen in patients with a transthoracic approach.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies suggested that diuretics are only useful in patients with ARDS and their effect in other patients is limited ( 1 , 4 , 45 ). In the past, fluid intake restriction and the use of diuretics were not recommended for patients who were diagnosed with NPPE ( 4 , 45 , 57 ). Since these patients are deficient in effective circulating blood volume owing to the transfer of large amounts of fluid to the lungs, this may aggravate their present state ( 57 ).…”
Section: Treatmentsmentioning
confidence: 99%